Comparing the Validity and Reliability of Place Attachment Across Cultures. Issue 11 (2nd November 2017) - Wynveen, Christopher J.; Schneider, Ingrid E.; Cottrell, Stuart; Arnberger, Arne; Schlueter, Alexander C.; Von Ruschkowski, Eick
ABSTRACT: Researchers often measure human–place bonds via place attachment scales across a variety of settings. However, scale use does not always include an evaluation of the scales' psychometric properties, especially in multisite studies. Failure to consider a place attachment scale's measurement properties makes both validity and reliability assumptions and may lead to improper data interpretation. Hence, this investigation assessed a place attachment scale across three sites via data collected on site in natural resource protected areas in Colorado, Minnesota, and Germany. A series of confirmatory factor analyses assessed the hypothesized two-dimensional (i.e., place identity and place dependence) model, Cronbach's alphas calculated a measure of internal consistency, and a multigroup procedure cross-validated the scale. Some items did not load on the hypothesized dimension and the pattern of factor loadings was not equivalent across settings, suggesting assessment of place attachment scales may be necessary when used in new contexts.